EFFECT OF MEDIA AND HORMONES ON ROOTING OF AFRICAN MARIGOLD STEM CUTTINGS IN MIST CHAMBER - D. APARNA*, M. L. N. REDDY, A. V. D. DORAJEE RAO, V. V. BHASKAR, P. SUBBARAMAMMA; K. UMA KRISHNA (The Journal of Research ANGRAU, 2021)
Experiments conducted from 2017 to 2019 (to find out suitable media and hormones for better rooting and establishment of marigold terminal cuttings for summer cultivation) revealed that cocopeat among media and IBA @ 3000 ppm as powder among hormonal treatments are the best which recorded highest percentage of rooted cuttings (75.00%, 95.10% ), highest number of roots per cutting (122.68, 174.90 ), maximum survival percentage of rooted cuttings (77.96%, 96.62% ), root length (4.64 cm, 5.62 cm ) and percentage establishment of rooted cuttings in main field (76.03%, 95.58%), respectively. Among the interaction effects, cocopeat and IBA @ 3000 ppm as powder recorded the maximum values for percentage of rooted cuttings (98.00%), number of roots per cutting (174.90), primary roots per cutting (11.58), secondary roots per cutting (114.6), longest root (5.62 cm), fresh weight of roots (1.68 g), dry weight of roots (0.60 g), root to shoot ratio (1.25), survival percentage of rooted cuttings (96.62%) and percentage establishment of rooted cuttings in main field (95.58 %). Whereas, cocopeat, NAA 200 ppm and their combination recorded the maximum shoot length (16.07 cm, 22.86 cm and 23.49 cm ) and highest number of leaves per rooted cutting (153.73, 184.80 and 197.55), respectively. The lowest values for all the parameters were recorded in sand medium alone without any hormonal treatments.